2004
DOI: 10.1172/jci200420216
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced neuronal excitability in the absence of neurodegeneration induces cerebellar ataxia

Abstract: Cerebellar ataxia, a devastating neurological disease, may be initiated by hyperexcitability of deep cerebellar nuclei (DCN) secondary to loss of inhibitory input from Purkinje neurons that frequently degenerate in this disease. This mechanism predicts that intrinsic DCN hyperexcitability would cause ataxia in the absence of upstream Purkinje degeneration. We report the generation of a transgenic (Tg) model that supports this mechanism of disease initiation. Small-conductance calciumactivated potassium (SK) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 26 publications
1
58
0
Order By: Relevance
“…Overall, the results reported by Shakkottai et al (4) provide genetic evidence that firmly supports the idea that, in vivo, the firing rate of DCN neurons is indeed regulated by SK channels. These data go a long way toward removing any doubt that may have existed as to the role of SK channels as regulators of DCN firing (10).…”
Section: Some Thoughtssupporting
confidence: 76%
See 4 more Smart Citations
“…Overall, the results reported by Shakkottai et al (4) provide genetic evidence that firmly supports the idea that, in vivo, the firing rate of DCN neurons is indeed regulated by SK channels. These data go a long way toward removing any doubt that may have existed as to the role of SK channels as regulators of DCN firing (10).…”
Section: Some Thoughtssupporting
confidence: 76%
“…Even though the authors provided an excellent illustration of the immunohistochemical scale used to assess expression levels (ref. 4, Figure 5b), some caution is warranted when the level of transgene expression is assessed solely by immunohistochemistry, which is relatively nonquantitative. Regardless, Shakkottai et al very nicely demonstrated that SK3-1B expression in DCN neurons correlates with an increase in their firing rate consistent with an increase in firing rate seen when SK channels were exposed to a pharmacological inhibitor.…”
Section: Harry T Orrmentioning
confidence: 99%
See 3 more Smart Citations